Do investors disproportionately shed assets of distant countries during global financial crises? The role of increased uncertainty - Ahrend, Rudiger (OECD Publishing, 2013)
The global crisis of 2008-09 went hand in hand with sharp fluctuations in capital flows. To some extent, these fluctuations may have been attributable to uncertainty-averse investors indiscriminately selling assets about which they had poor information, including those in geographically distant locations. Using a gravity equation setup, this article shows that the impact of distance increases with investors' uncertainty aversion. Consistent with a sudden increase in uncertainty, the negative impact of distance on foreign holdings increased during the global financial crisis of 2008-09. Host-country structural policies enhancing the quality of information available to foreign investors, such as strict disclosure requirements and prudential bank regulation, tended to mitigate withdrawals